"Mannose glycans as key players in trained immunity: A novel anti-tumoral catalyst" - Almeida, P (2025)
Cell wall glycans isolated from microorganisms are long known to provoke strong immune responses piloted by innate immune cell populations, including monocytes, in the context of Trained Immunity (TI). However, the contribution of yeast-derived mannan in the reprogramming of monocytes remains ill-defined. Here, we demonstrated that TI is often accompanied by an altered gene expression profile of selected glycan-binding proteins expressed by monocytes, including DC-SIGN and Dectin-2. Additionally, we showed that mannan, a mannose rich glycan, can trigger an enhanced immune phenotype compatible with TI in healthy monocytes, with glycan-primed cells exhibiting enhanced pro-inflammatory cytokine secretion (TNFα and IL-6) and higher activation (CD86) levels. Furthermore, the glycan-mediated priming of monocytes also imposed alterations to the expression of certain Glycan-Binding Proteins, such as DC-SIGN. Importantly, we established that these mannan-trained immune cells displayed an improved capacity to kill tumor cells in vitro. Lastly, we confirmed that monocytes from non-muscle invasive bladder cancer patients treated with BCG instillations presented a TI phenotype, as was revealed by the higher cytokine production and activation. Altogether, this study lays the foundations for exploiting the immunological potential of glycan-derived pathogens in reprogramming innate immune cells towards an effective anti-tumor immune response.